2022
DOI: 10.1177/19418744211067043
|View full text |Cite
|
Sign up to set email alerts
|

Neurology Morbidity and Mortality Conferences and Quality Improvement: Single-Center Experience and National Survey

Abstract: Background Morbidity and Mortality (M&M) conferences are widespread but vary in goals and methodology. Some focus on clinical enigmas while an increasing number utilize quality improvement (QI) tools to effect systems change. Little is known about the current state of US Neurology M&Ms. Methods We surveyed 56 US academic neurology departments regarding their M&Ms to understand the use of QI tools and assess variability. Additionally, we reviewed the evolution of M&Ms in our department. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…33 It is important to note that they attribute these successes to their organizational culture, motivation, commitment, communication and inherent skills, rather than the format of the M&M. 33 In line with their findings, another survey-based study attributed success of their M&Ms to the incorporation of a just culture, peer review protection, use of a quality improvement methodology, and logistical optimization. 34 The Ottawa M&M Model contains multiple components but involves training physicians in appropriate case selection and case analysis, interprofessional involvement, an M&M facilitator, and an M&M "bottom line" that is disseminated and later acted on through quality committees. 35 A group of nephrologists used the Ottawa M&M Model and showed that more than half of all conferences held by this group yielded action items and recommendations that led to improved care delivery.…”
Section: Goal(s) Of Mandms and Measures Of Successmentioning
confidence: 99%
“…33 It is important to note that they attribute these successes to their organizational culture, motivation, commitment, communication and inherent skills, rather than the format of the M&M. 33 In line with their findings, another survey-based study attributed success of their M&Ms to the incorporation of a just culture, peer review protection, use of a quality improvement methodology, and logistical optimization. 34 The Ottawa M&M Model contains multiple components but involves training physicians in appropriate case selection and case analysis, interprofessional involvement, an M&M facilitator, and an M&M "bottom line" that is disseminated and later acted on through quality committees. 35 A group of nephrologists used the Ottawa M&M Model and showed that more than half of all conferences held by this group yielded action items and recommendations that led to improved care delivery.…”
Section: Goal(s) Of Mandms and Measures Of Successmentioning
confidence: 99%